FEMALE RELIGIOUS AUTHORITY, RELIGIOUS MINORITY AND THE AHMADIYYA: The Activism of Sinta Nuriyah Wahid (JOURNAL OF INDONESIAN ISLAM, 2015)
In the present-day Indonesia, cases of discrimination and violence towards minorities are still prevailing. A number of Indonesian personages who play a strong role in defending minorities have been observed, most particularly Muslim minority groups such as the Shi’ism and the Ahmadiyya. One of these personages: Sinta Nuriyah Wahid (b. 1948). One may say that Sinta is a female Muslim scholar-activist who is rooted in traditionnalist Islam, and accordingly is considered a figure of authority in speaking in the name of Islam. This article is dealing with the role and authority of this female scholar-activist in promoting the rights of the Ahmadiyya in contemporary Indonesia. The first concern of this paper is dealing with Sinta’s roles in protecting the Ahmadiyya in Indonesia. The second concern is dealing with the ways in which Sinta and her ideas on protecting the Ahmadiyya wield authority on present-day Indonesian Muslims.